Oligarchy vs. Sovereignty: Constitutional Amendments and the Democratic Regression of Indonesia’s Post-Reform Era - Amiludin Amiludin; Bahtiar Amrullah; Tajudeen Sanni; Zaharuddin Sani Ahmad Sabri; Bayangsari Wedhatami (Indonesian Constitutional Studies, 2025)
This study examines the paradoxical role of Indonesia’s post-Reform constitutional amendments, which, while designed to enhance democracy, have inadvertently facilitated oligarchic capture and democratic regression. The primary objective is to analyze how constitutional design, though formally advancing popular sovereignty, created institutional arrangements that allowed entrenched elites to mediate, constrain, and often subvert the people’s will. Employing a doctrinal legal method complemented by comparative and conceptual analysis, the research evaluates Indonesia’s constitutional amendments of 1999–2002, relevant statutes, and Constitutional Court jurisprudence, situating these within broader global patterns of democratic backsliding in Latin America, Eastern Europe, and the United States. The analysis integrates theoretical insights from Robert Dahl’s polyarchy, Michael Walzer’s spheres of justice, and Jeffrey Winters’ theory of oligarchy to illuminate the nexus between economic power and political sovereignty. The findings reveal that while the amendments formally entrenched rights, strengthened checks and balances, and institutionalized elections, they simultaneously empowered political parties as gatekeepers, entrenched money politics, weakened oversight institutions such as the Constitutional Court and Corruption Eradication Commission, and left socio-economic inequalities unaddressed. These dynamics have gradually hollowed out the substantive content of sovereignty, embedding oligarchic dominance within constitutional practice. The study concludes that reform-oriented constitutionalism must extend beyond textual guarantees to address structural inequalities, democratize political parties, fortify accountability institutions, and embed participatory safeguards. By integrating lessons from comparative constitutionalism, Indonesia can reimagine its constitutional order to resist oligarchic entrenchment and reclaim the democratic promise of Reform.